A water accounting procedure to determine the water savings potential of the Fergana Valley - Karimov, A.A.; Molden, David J.; Khamzina, T.; Platonov, Alexander; Ivanov, Y. (Elsevier, 2012)
The Syrdarya River basin in Central Asia exhibits symptoms of scarcity because of growing competition between hydropower upstream and environment, cities and agriculture downstream. Different approaches to water management, based on water savings in agriculture could relieve the stress of competition, yet keep alive a vibrant agriculture. The Fergana Valley, a highly productive area within the upstream of the Syrdarya River, was analyzed to determine the water savings potential of agriculture. This paper used a water accounting procedure to identify both the scope for savings and the strategies to realize those gains. Significant nonproductive depletion of water at 2681–4164 million m3 (Mm3) was identified in the form of evaporation, flows to sinks and pollution. The water-saving potential is estimated at 2823 Mm3 annually, which is about 10% of the total inflow into the area, through a range of practical approaches. This strategy would bring regional benefits by reallocation of surplus winter flow from the upstream for summer use in the downstream.